Efficacy of Using Problem-Solving Method on the Teaching of Social Studies in Public Primary Schools in Busiki County Namutumba District - Waiswa, Mark Micheal (East African Journal of Education Studies, 2024)
The study sought to establish the efficacy of using a problem-solving approach in teaching social studies in Busiki County, Namutumba District, responding to three questions; (1) how a problem-solving method is used in the teaching of social studies? (2) What are the implications of using the problem-solving method in the teaching of social studies? (3) What are the hindrances to the use of problem-solving methods in the teaching of social studies? The study was conducted using a quasi-experimental design and targeted public primary schools in Busiki County. The study population mainly comprised teachers who are the direct implementers of the approach. Questionnaires were used to obtain findings from 99 respondents purposively selected. According to the findings, the problem-solving method can be used to teach social studies in five main ways: critical thinking, historical studies, multiple analyses of events, using secondary sources of information, and using logical examples. The implications are: promoting critical thinking; developing skills for learners to face the real world; developing the ability to make evaluations; making learning more engaging; and promoting the sharing of ideas. The hindrances include; No platform for professional development, scepticism, no teaching aids, and No integration into the curriculum. Conclusively, the problem-solving method is an effective approach for teaching social studies in primary schools. It is therefore recommended that educational leaders try to consider the significance of incorporating critical thinking into social studies instruction, despite challenges like a lack of professional knowledge and scepticism